Educational Attainment Level and Risk of Mortality and Cardiopulmonary Outcomes in High‐Risk Patients With Cardiovascular Disease: The INVESTED Trial - Mats C. H. Lassen; Nicholas Howell; Brian L. Claggett; Tor Biering‐Sørensen; Orly Vardeny; Scott D. Solomon; Jacob Udell; Jacob Joseph; Sheila M. Hegde (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Educational attainment level (EAL) is an indicator of socioeconomic status and has been shown to be inversely related with adverse health outcomes. However, the association between EAL and risk of clinical outcomes in high‐risk patients with cardiovascular disease has not been extensively investigated. Methods In the INVESTED (Influenza Vaccine to Effectively Stop Cardio Thoracic Events and Decompensated Heart Failure) trial, patients with recent heart failure or myocardial infarction hospitalization were randomized 1:1 to high‐dose trivalent or standard‐dose quadrivalent influenza vaccine from September 2016 to January 2019. We examined the association between EAL and risk of clinical outcomes for each participant across all enrolling seasons using adjusted Cox models stratified by trial entry season. Participants were categorized by EAL (≤high school, post‐high school or trade, and ≥college). Results Of the 4912 participants (mean age: 65.5 years, 28% female, 80% White) with EAL information, 43% had high school, 29% had post‐high school or trade, and 28% had ≥college as EAL. Those with higher EAL were more likely to be White or Asian, be married/with long‐term partner, have higher left ventricular ejection fraction, have lower New York Heart Association class, and less likely to have comorbidities and risk factors than those with lower EAL. During follow‐up (median: 9 months), 1706 (35%) participants experienced the composite of all‐cause death or cardiopulmonary hospitalization. Compared with high school, higher EAL was associated with a stepwise decrease in risk (post‐high school or trade: hazard ratio [HR], 0.88 [95% CI, 0.79–0.99]; ≥college: HR, 0.71 [95% CI, 0.63–0.81], Ptrend <0.001). Conclusions High EAL is significantly associated with a decreased risk of adverse clinical outcomes in patients with high‐risk cardiovascular disease after adjustment for other key risk factors, highlighting the need to consider EAL in risk assessment and target additional resources toward those with low EAL to improve prognosis. Registration URL: https://clinicaltrials.gov; Unique identifier: NCT02787044.